Cytotoxic effect of different Uncaria tomentosa (cat’s claw) extracts, fractions on normal and cancer cells: a systematic review - Lopes, Adriana A.; Coppede, Juliana da Silva; Amatto, Pedro de Pádua G.; Aragon, Davi Casale; França, Suzelei de Castro; Carmona, Fabio; Pereira, Ana Maria S. (Frontiers in Pharmacology, 2025)
BackgroundUncaria tomentosa (cat’s claw) is a medicinal plant with documented immunomodulatory and anti-inflammatory properties. Recent studies suggest potential anticancer effects, but evidence remains fragmented.ObjectiveThis systematic review aimed to assess the cytotoxic effects of different U. tomentosa extracts or fractions on normal and cancer cells, summarizing in vitro studies.MethodsA systematic search was conducted in PubMed, Embase, and Scielo up to January 2025, following PRISMA guidelines. Inclusion criteria comprised in vitro studies evaluating U. tomentosa extracts or fractions on normal and cancer cells, reporting IC50 values or equivalent measures. Data on plant part, extraction method, and chemical composition were collected. Risk of bias was assessed using the modified CAMARADES checklist.ResultsThirteen studies met the eligibility criteria. U. tomentosa extracts exhibited selective cytotoxicity in some cancer cell lines. The most promising findings were observed for crude aqueous bark extracts (72 h incubation) against squamous cell carcinoma and pentacyclic oxindole alkaloid (POA)-rich extracts against prostate cancer and leukemia. In contrast, tetracyclic oxindole alkaloid (TOA)- and proanthocyanidin (PAC)-rich fractions showed limited cytotoxicity. Most extracts were non-toxic to normal cells, except for the crude aqueous bark extract, which exhibited cytotoxicity in keratinocytes.ConclusionU. tomentosa has potential as a source of selective anticancer agents, particularly through crude aqueous bark and POA-rich extracts. The observed cytotoxic effects vary considerably depending on the extraction method and chemical composition, underscoring the need for standardization in future studies. Further standardized studies and mechanistic investigations are required to validate its therapeutic potential for cancer treatment.Systematic Review Registrationhttps://osf.io/hfazq/.